A scale for CEO personal brand measurement - Hai-Ming Chen; Hsin-Mei Chung (South African Journal of Business Management, 2017)
A Chief Executive Officer (CEO) is important for the image and culture of a business. His/her personal brand improves the brand of the business and also has a halo effect on customers and employees both present and potential. In order to better understand the effects that a CEO's personal brand may have on a business, it is necessary to identify the key dimensions or variables that determine personal brand for business leaders. Most of the research on personal brand so far has been restricted to the area of how to build up one's own personal brand. In this article personal brand is conceptualized as a multi-dimensional cognitive affective phenomenon. The current research presents a pilot study suggesting a seven-dimension scale to measure a CEO's personal brand. This unique, reliable scale is viable and could assist boards of directors in confirming whether a CEO's personal brand meets the expectations of the enterprise.
Keywords: 650